1999
DOI: 10.1021/jo990442x
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-Diels−Alder Reactions of Homochiral 1,2-Diaza-1,3-butadienes with Diethyl Azodicarboxylate under Microwave Irradiation. Theoretical Rationale of the Stereochemical Outcome

Abstract: The stereoselective normal electron demand Diels-Alder reactions of chiral 1,2-diaza-1,3-butadienes, derived from acyclic carbohydrates having different configurations (1-6), with diethyl azodicarboxylate (DEAD) are disclosed. Reactions proceed slowly in benzene solution at room temperature, but are greatly accelerated by microwave irradiation to form the corresponding functionalized 1,2,3,6-tetrahydro-1,2,3,4-tetrazines (7-18) in good yields. The observed stereoselectivity is markedly dependent on the relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 38 publications
(28 reference statements)
1
17
0
1
Order By: Relevance
“…12 As we shall see, and in a counter-intuitive way, it appears that the second stereocenter exerts a strong stereoface directing effect with respect to the heterocyclic dipole. Again, a computational study at a semiempirical level is sufficient to provide a satisfactory rationale of the stereochemical outcome, thereby validating models previously suggested for the interpretation of [3 + 2] cycloadditions.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…12 As we shall see, and in a counter-intuitive way, it appears that the second stereocenter exerts a strong stereoface directing effect with respect to the heterocyclic dipole. Again, a computational study at a semiempirical level is sufficient to provide a satisfactory rationale of the stereochemical outcome, thereby validating models previously suggested for the interpretation of [3 + 2] cycloadditions.…”
Section: Introductionmentioning
confidence: 74%
“…8,12 The main argument, illustrated in Scheme 3, for the observed face selectivity is based on the assumption that the acyloxy group attached to the first stereocenter moves away from the heterocyclic dipole. It is worth noting that in acyclic sugar heterodienes in which the first stereocenter has the opposite configuration, the face exposed for attack has been observed to be the Si,Si face.…”
Section: Resultsmentioning
confidence: 99%
“…This property of graphite has been exploited in the microwave-assisted one-pot synthesis of cyanuric acid ( [1,3,5] triazine-2,4,6-triol), prepared via pyrolysis of urea in the absence of water and organic solvents (Scheme 3.39) 64 . The authors suggested that the higher yields and short reaction rates observed in this study were the direct consequence of localised superheating (often called 'hot spots' Avalos et al has reported the microwave-assisted synthesis of tetrazine derivatives by a hetero Diels-Alder reaction of homochiral 1,2-diaza-1,3-butadienes with diethyl azodicarboxylate (Scheme 3.40) 65 . Under conventional conditions, reactions could be performed in benzene solution at room temperature.…”
Section: Triazines and Tetrazinesmentioning
confidence: 84%
“…26 The dienes are reacted with DEAD to give the corresponding hetero-Diels-Alder cycloadducts in good to excellent yields (87 -96%) and good diastereoselectivities. …”
Section: Synthesis Of Tetrazinesmentioning
confidence: 99%